Ketertarikan Penggunaan Go-Pay di Kalangan Mahasiswa Dilihat dari Pengaruh Persepsi Kegunaan dan Persepsi Kemudahan - Simarmata, Hengki Mangiring Parulian; Pardede, Henry Dunan; Simarmata, Poltak Pardamean; Saragih, Doris Yolanda (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the magnitude of the influence of perceived usefulness and perceived ease of use of Go-Pay among Indonesian Business Polytechnic students. The research was carried out quantitatively by collecting primary and secondary data from distributing questionnaires and observations. The population is all students of the Indonesian Business Polytechnic who use Go-Pay and the sample used was 100 students. Data was collected and tested for validity, reliability, normality and other tests, hypothesis testing was carried out using the t test and F test. The research results showed that both simultaneously and partially the perception of usefulness and the perception of convenience had a significant positive influence on the use of the Go-swallow e-wallet. Pay. The magnitude of the influence of the two variables on interest in using Go-Pay is 60.8%. This study can be developed by expanding the research object and researching the use of other developing financial technologies.